2022
DOI: 10.3390/jof8010087
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Colletotrichum Species from Aquatic Plants in Southwest China

Abstract: Colletotrichum species are plant pathogens, saprobes, and endophytes in many economically important hosts. Many studies have investigated the diversity and pathogenicity of Colletotrichum species in common ornamentals, fruits, and vegetables. However, Colletotrichum species occurring in aquatic plants are not well known. During the investigation of the diversity of endophytic fungi in aquatic plants in southwest China, 66 Colletotrichum isolates were obtained from aquatic plants there, and 26 of them were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…Liu et al (2022) accepted 280 species in 16 species complexes and 15 singleton species and established a genome tree comprising 94 species. Further 13 species were added by Alizadeh et al (2022), Hassan et al (2022) and Zheng et al (2022).…”
Section: Pararamichloridialesmentioning
confidence: 99%
“…Liu et al (2022) accepted 280 species in 16 species complexes and 15 singleton species and established a genome tree comprising 94 species. Further 13 species were added by Alizadeh et al (2022), Hassan et al (2022) and Zheng et al (2022).…”
Section: Pararamichloridialesmentioning
confidence: 99%
“…Secondly, because the Colletotrichum genus is one of the most important pathogenic fungi [33], our finding highlighted the high disease risk driven by invasive plants in the invaded ecosystem. Indeed, some of these Colletotrichum species were previously verified to be pathogenic on local native plants [32], as well as on tested fruits, including grape and mango, as the recent research by Zheng et al [82] also revealed. This result suggested that invasive species can facilitate pathogen emergence and amplification, raising concerns about the movement of pathogens among agricultural, horticultural and wild grasses.…”
Section: Discussionmentioning
confidence: 81%
“…Subsequently, many Colletotrichum species had been successfully identified and epitypified, resulting in a much better understanding of phylogenetic relationships of this genus ( Weir et al 2012 ; Damm et al 2014 ). Currently, more than 1000 Colletotrichum epithets are listed in Index Fungorum ( http://www.indexfungorum.org ), and at least 303 species, grouped in 16 species complexes and some singleton species ( Mu et al 2021 ; Alizadeh et al 2022 ; Liu et al 2022 ; Zheng et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%